Biliary ochratoxin A as a biomarker of ochratoxin exposure in laying hens: An experimental study after administration of contaminated diets. (June 2015) - Armorini, Sara; Al-Qudah, Khaled Mefleh; Altafini, Alberto; Zaghini, Anna; Roncada, Paola
Highlights: Two groups of laying hens were fed with 10 and 200 µg/kg ochratoxin A diet. We studied the occurrence of ochratoxin A (OTA) in kidney, liver, bile, and eggs. The level of OTA in the eggs of the two groups was below the limit of detection. OTA levels detected in bile were much higher than in kidney and liver. OTA in bile could be a biomarker for OTA levels in edible tissues of poultry. Abstract: To evaluate the levels of ochratoxin (OTA) in kidney, liver and bile of laying hens, forty-five laying hens were enrolled in this study and divided into three equal groups: a control group D0, and two experimental groups, D1 fed with 10 µg/kg OTA diet and D2 fed with 200 µg/kg OTA diet for 6 weeks. Kidneys, livers, and bile from all hens were collected and analyzed by HPLC method for the presence of OTA. Eggs collected 2 days before the start of the experiment and 2 days after its end were also analyzed for the presence of OTA. Results show a relevant biliary excretion of the mycotoxin, with high levels of OTA in the bile after administration of the toxin. OTA level in eggs was below the limit of detection (LOD). These results suggest the suitability of using bile as a matrix for screening measurements of OTA in laying hens.